Strategi Desain Sentra Lokakarya dan Taman Evokatif Guna Meningkatkan Tingkat Perekonomian di Kabupaten Wonosobo - Muhamad Hanif Dwi Putra; Rachmadi Nugroho; Ofita Purwani (ARSITEKTURA, 2019)
The workshop center and the evocative park is training, developing, and marketing space for the regional economic industry’s product innovation to raise the level of regional economy. Wonosobo is a region in Indonesia with low economic level and high poverty rates.  Even though Wonosobo has a lot of potential regional economic industries but local people tend to choose to look for economic opportunities in urban areas. In order to be able to attract local people to develop regional economic industries and evoke consumers to come and buy, the workshop center and evocative park must have an optimal level of transparency to provide a comfortable working environment and apply consumer behavior criteria to evoke the feeling of consumers. The optimal level of transparency can be shown in the selection of building materials and spatial organization. While criteria for consumer behavior can be shown in the spatial circulation. The method is to make a focus group discussion to make a mapping of potentials and problems in the Selomerto subdistrict in order to get potential regional economic industries to be developed and apply transparency and consumer behavior criteria to make a comfortable working environment and evoke consumers.